Public Agitation, Social Media and the Government: An Analysis of the Use of Social Media as a Catalyst for Change in Nigeria - Sope Williams-Elegbe (Unilag Journal of Humanities, 2019)
Many countries in Sub-Saharan Africa have enjoyed a political and economic renaissance in the last 25 years. Politically, many countries have enjoyed relative democratic stability and the economic benefits that accompany democratic rule. It is generally assumed that a stable democracy is synonymous with responsible (or at- least, more responsible) leadership, howsoever defined. One country that appears to deny this assumption is Nigeria. An assessment of the type of leadership that Nigeria has endured since 1999, illustrates that the Nigerian democracy does not appear to be attracting the kind of leadership that can translate political rhetoric into developmental benefits. There are several reasons for this, which include the educational constraints; the vestiges of military governance, which has limited the collective awareness of appropriate leadership styles as well as the funding mechanism for political office, which excludes the intelligentsia and the middle class from ejJectively participating in the political process amongst others. This paper presents a critical assessment of public agitation for good governance, as stimulated by social media in Nigeria between 2009 and 2014. 1t will examine social media responses to leadership failings in Nigeria and determine whether citizen responses are able to provide a catalyst for a change. The paper will conclude with an assessment of citizen-led measures that may work, are working or have worked in Nigeria that may affect the quality and nature of leadership in Nigeria.